Muhammad Ali Al-Abed and his Political Role in Syria 1867-1939 - Abdulkarim, Lamia Malik; Hamdan , Mariam Abd Ali (Journal of Ecohumanism, 2024)
Muhammad Ali Al-Abed is a quiet but powerful figure in Syria. He was well-known in science and widely respected in the Arab world and abroad due to his deep expertise in politics, culture, and diplomacy. He held a number of positions in the Ottoman Empire, including ambassador to France and the United States of America. From an early age, he was trained by experienced teachers, and his mother tried to emphasize his unique appearance. the Ottoman Empire and other nations, and that Al-Abed was a wealthy Syrian who spoke Arabic, Turkish, French, Old Ottoman, Persian, and English with ease. Abed studied in Damascus, Beirut, Istanbul and Paris, which he left as a child, worked in the Ottoman Ministry of Foreign Affairs and was appointed ambassador to the United States of America, and after the coup against Sultan Abdul Hamid II in 1908, he and his family never returned to the Ottoman Empire, instead, the family moved around Europe until the end of World War I, then settled in Egypt and then returned to Damascus After the start of the Mandate, the neutrality of the political dimension and his good relations with the Mandate loyalists on the one hand And the national group on the other hand to his inauguration as president on June 13, 1932, and was the first person in Syria to assume the post of President of the Republic, and due to the lack of a constitution adopts the republican system, he called his predecessors the title of "heads of state", and according to the constitution the term of the presidency is five years, but he resigned in 1936 because of his age in preparation for the start of the rule of ethnic groups after the signing of the Syrian-French treaty, during his presidency, four successive governments were formed.